Electrical substation design and engineering - Liew, Yew Sheng (2019)
The electrical power substation in power generation plant, transmission or distribution also consist apart of very important in electric power engineering. The objective of carrying out this research are to provide overview of electrical substation, reference and guides to the design information. To provide some useful information from initial concept of design, data extraction, calculation, material selection, automation, operation method, protection devices and etc. Besides, this research also contain of most recent technology development which related to industry practice, requirement and standards. During design of an Electrical Substation, some aspects must be taken into consideration: • Low capital cost • Reliability of the facilities • Low operating cost • High Efficiency • Simplicity of design • Reserve capacity for future expansion